PENGARUH PENAMBAHAN TEMPE TERHADAP TIGKAT KESUKAAN DAN DAYA SIMPAN NUGGET IKAN NIKE (Awaous melanocephalus) - Liputo, Sitti Aisa; Berhimpon, S.; Fatimah, Fetti (Pascasarjana Unsrat, 2013)
The study of fish nugget snike (Awaous melanocephalus) with the substitution of tempe has beendone. Four formulations of nike and tempe ratio were observe, i.eformula A1 (100% nike: 0% tempe) A2(75% nike: 25% tempe), A3(50% of nike: 50% tempe), and A4 (25% of nike: 75% tempe). Organoleptic assesment was done to obtain the most preferred formula. Assesment on the effect of tempe to the shelf life of nugget, where also conducted. Quality parameter estimated were TPC, TBA, TVBN, and pH. Data were analyzed using a completely randomized design, faktorial 4x3 dan 3x ulangan, treatments was test educing Annovawith 0.05, for significant effect testedusing Duncan's multiple rangetest (DMRT). The result showed that the most preferred formulation by the panel ists wasthe formula A2. The longest shelf life was the formula A4, which up to 20 days of storage. TBA value also shown the same results as of TPC, the lowest TBA(0057 mg malonaldehid/100 g samples) until 20 days of storage